2013
DOI: 10.3989/scimar03702.10a
|View full text |Cite
|
Sign up to set email alerts
|

Baseline study of the distribution of marine debris on soft-bottom habitats associated with trawling grounds in the northern Mediterranean

Abstract: SUMMARY: The present study aims to analyse the local and regional variability in the density and typology of marine debris on fishing grounds on the northern Mediterranean continental shelf, and to test relationships between marine litter and trawl fishing activity. Moreover, the colonization of plastics was examined in order to study the importance of plastics as a source of impact on marine communities and their further environmental implications. This study surveyed 11 sites, associated with trawling ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 26 publications
2
27
1
Order By: Relevance
“…The process of colonization causes density changes in MPD, which, in combination with the effect of currents, may cause their sinking to the seabed. Once on the seabed, the process of colonization continues (Fortuño et al 2010, Demestre and Masó 2012, Sánchez et al 2013. Not only macroplastics but also microplastics are subject to microfouling (Reisser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The process of colonization causes density changes in MPD, which, in combination with the effect of currents, may cause their sinking to the seabed. Once on the seabed, the process of colonization continues (Fortuño et al 2010, Demestre and Masó 2012, Sánchez et al 2013. Not only macroplastics but also microplastics are subject to microfouling (Reisser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In each study area, 18 dredge samples were randomly collected performing a 15-minute tow at 2.5 kn following the sampling strategy used in epibenthic studies (de Juan et al 2011). In a previous analysis conducted on these samples, Sánchez et al (2013) showed that only 8% of collected plastics showed no sign of colonization, while the rest were covered by fouling organisms. A subset of 16 benthic plastics, in the first phase of succession of colonization, was selected to be analysed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations